LEGAL PROTECTION FOR DENTISTS IN HANDLING PATIENTS IN CASES OF TOOTH EXTRACTION WITHOUT INFORMED CONSENT (STUDY AT VARIOUS INDEPENDENT PRACTICE PLACES FOR DENTISTS IN PEMATANGSIANTAR) - Hargo Basuki; Bambang Fitrianto; Dahlan (PT. Radja Intercontinental Publishing, 2024)
This study aims to determine and analyze legal regulations regarding the obligation of informed consent in tooth extraction services, the responsibility of dentists towards patients in providing informed consent in cases of tooth extraction and legal protection for dentists in handling patients in cases of tooth extraction without informed consent in various places. Independent practice of dentist in Pematangsiantar. The method in this research uses descriptive analytical empirical juridical research. The data sources obtained used primary data and secondary data. The data collection technique used is library research. The results of this research reveal that legal regulations regarding the obligation of informed consent in tooth extraction services by dentists in Indonesia have been regulated in various laws, including Law no. 36 of 2009 concerning Health, Law no. 44 of 2009 concerning Hospitals and now Law no. 17 of 2023 concerning Health. The dentist's responsibilities include providing sterile tools and materials, examining the patient's medical history, and carrying out extractions according to SOP and competency. Legal protection for dentists in cases of extractions without informed consent in Pematangsiantar reflects awareness of the importance of informed consent. UU no. 17 of 2023 emphasizes two principles of legal protection: preventive and repressive. If the dentist does not carry out the obligation to carry out informed consent, there could be civil and criminal consequences. This study recommends that every dentist provide informed consent in treating patients.